Heritability estimations for growth characters and size of the cardiorespiratory organs in Arctic charr (Salvelinus alpinus) - Montañez, M.A.; Ginés Ruiz, Rafael; Navarro Guerra,Ana; Afonso López, Juan Manuel; Thorarensen, H. (Aquaculture, 2007)
S290 S290 1 1,735 Q1 SCIE